Impact of regional differences in stroke symptom awareness and low-income status on seeking emergency medical service in China. Issue 15 (5th August 2021) - Yuan, Jing; Shan, Guang-Liang; Li, Sheng-De; Gao, Chun-Peng; Cui, Li-Ying; Peng, Bin
Abstract: Background: Unawareness of stroke symptoms and low income are two barriers that affect the seeking of emergency medical service (EMS). This study aimed to assess the effect of unawareness and low income on seeking EMS and to investigate the regional distribution of the unawareness and low-income status and their associations with failing to call EMS in China. Methods: A total of 187, 723 samples from the China National Stroke Screening Survey was interviewed cross-sectionally. Four status of awareness and annual income were identified: unaware and low-income, unaware-only, low-income-only, and aware and regular income. The outcomes were whether they intended to call EMS or not. The regional distribution of each status and their associations with not calling EMS were presented. Results: The status of unaware and low-income, unaware-only, and low-income-only accounted for 6.3% (11, 806/187, 673), 11.9% (22, 241/187, 673), and 21.5% (40, 289/187, 673) of the total sample, respectively. Not calling EMS was significantly associated with the status of unaware and low-income (odds ratio [OR]: 3.21, 95% confidence interval [CI]: 3.07–3.35), unaware-only (OR: 2.38, 95% CI: 2.31–2.46), and low-income-only (OR: 1.67, 95% CI: 1.63–1.71), compared with the aware and regular income status. The Midwest regions had higher percentages of people in the unaware and low-income status; the East, South, and Central had higher percentages of unaware-only status; the North and Northeast regions had a higher percentage of low-income-only status, compared with other regions. Conclusion: The existence of the regional difference in unawareness and low income justifies the specific stroke education strategies for the targeted regions and population.